ANALISIS PENGUJIAN KAPASITAS BATERAI 110 VOLT GROUP 2 (SISTEM 500 KV) GITET MANDIRANCAN - Idris Afandi; Rahmat Hidayat; Insani Abdi Bangsa (Politeknik Harapan Bersama Tegal, 2021)
Abstract Battery is a DC system device, its existence is very important in the world of electricity to maintain the stability of the DC system. Battery function in Extra High Voltage Substation (GITET) as a backup to supply DC device components such as relays, PMS (Disconnecting Switch), PMT (Voltage Breaker), and SCADATEL telecommunication devices. In the event of blackout, the rectifier does not get a power supply whose function is to convert the AC to DC power current to meet the needs of the DC device lsitrik supply remains active and working, so that the battery that replaces the role of the rectifier to maintain the stability of the DC system until the repair is complete. To maintain the stability and feasibility of battery function, routinely conducted tests on batteries carried out once every 2 years. This paper will compare the data of test results conducted in 2018 and 2020. From the results of the comparison data obtained the function of the state of the battery. Testing the battery capacity through 4 stages, floating is a battery in a full charger does not receive and emits current under normal circumstances the battery is connected to the rectifier. Equalizing aims to equalize and level the voltage value on each battery cell. Dischaerge Battery is a battery testing process to obtain a total efficiency capacity value (Ah) of the battery. When the battery is discharged large, the next step is boosting to restore the voltage value at a normal state (floating) 1.40-1.44 volts.